2018
DOI: 10.3389/fphar.2018.00933
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Occurrence of Proarrhythmic Afterdepolarizations in Atrial Versus Ventricular Cardiomyocytes: Implications for Translational Research on Atrial Arrhythmia

Abstract: Background: Principal mechanisms of arrhythmia have been derived from ventricular but not atrial cardiomyocytes of animal models despite higher prevalence of atrial arrhythmia (e.g., atrial fibrillation). Due to significant ultrastructural and functional differences, a simple transfer of ventricular proneness toward arrhythmia to atrial arrhythmia is critical. The use of murine models in arrhythmia research is widespread, despite known translational limitations. We here directly compare atrial and ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…S3B, C). The fixed cTnT+ cells from the Atrial (D1RA) differentiations were also significantly smaller than the fixed cells from the ventricular differentiations (7.9 µm vs. 13.4 µm, respectively), similar to what has been reported elsewhere [ 41 , 42 ], with relative profiles similar to freshly dissociated cells (Additional file 4 : Fig. S3A, D).…”
Section: Resultssupporting
confidence: 85%
“…S3B, C). The fixed cTnT+ cells from the Atrial (D1RA) differentiations were also significantly smaller than the fixed cells from the ventricular differentiations (7.9 µm vs. 13.4 µm, respectively), similar to what has been reported elsewhere [ 41 , 42 ], with relative profiles similar to freshly dissociated cells (Additional file 4 : Fig. S3A, D).…”
Section: Resultssupporting
confidence: 85%
“…Similarly, we have shown that leptin levels were significantly lower in patients with HFpEF and AF as compared to HFpEF without AF [ 24 ]. The mechanisms by which leptin impacts atrial electrophysiology remain incompletely understood.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the association of AF with the lower plasma concentrations of irisin may be due to the absence of irisin's inhibitory action on the sympathetic nervous system. Consequently, the imbalance in sympathetic tone to the heart creates a transitory dynamic proarrhythmogenic substrate which may trigger and initiate the AF [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Basically, a DAD occurs in response to a spontaneous SR Ca 2+ release event, expanding as a Ca 2+ wave through the cytosol and depolarizing the membrane, due to part of Ca 2+ being expelled from the myocytes via Na + /Ca 2+ exchanger (NCX) [15,16]. Repetitive ectopic activity initiates atrial arrhythmias in myocytes [17] and in whole hearts [18]. Thus, the most prominent channels causing ectopic activity are the ones responsible of the magnitude of the SR Ca 2+ loading and release, the SR Ca 2+ ATPase (SERCA2a) and ryanodine receptor 2 (RyR2) [14].…”
Section: Ectopic Activitymentioning
confidence: 99%